VISUAL ART EXPRESSION OF NEURODIVERGENT TEENS AGED 16 TO 20: A CASE STUDY - Alvizurez, Mairena Joanie Carissa Mairena; Balisnomo , Darla Monica; Anolin, Ann; Ramos , Rowena; Balila, Jolly; Naidas , Michael (12th International Scholars Conference 2025, 2026)
This qualitative case study examines how neurodivergent teenagers, aged 16-20, specifically those with Autism Spectrum Disorder (ASD), share their identities, feelings, and inner experiences through visual art. Utilizing the Expressive Theory of Art, the study highlights arts-based and participatory methods, including semi-structured interviews, artwork analysis, and observations in collaboration with a psychologist and professional artist.The study examines a small sample of three neurodivergent participants. The results indicate that visual art can serve as an important medium for expression, where each participant was able to articulate complex feelings and convey narratives that extended beyond linguistic forms of communication. The four themes of self-expression, emotional storytelling, symbolic imagining, and hybrid visual language contribute to a richer understanding of the inner worlds of these teens. Each participant's visual expression revealed unique coping strategies, individual personal symbols, and emotional depth that was not shared verbally. The findings of this research study add to a body of knowledge that explores the relationship between Autism and creative expression. Moreover, this study highlights the need for inclusive educational and therapeutic art practices to support neurodivergent adolescents in expressing their inner worlds. It is also recommended that future research continues with a broader range of participants, as each cognitively diverse teen demonstrates distinct and particular traits in their visual Art expressions.